EXPLORING LOCAL WISDOM THROUGH PROJECT-BASED LEARNING: A CASE STUDY OF THE APPLICATION OF ETHNOSCIENCE MODELS - Oria Lasmana1*, Festiyed2, Yerimadesi3, Abdul Razak4, Muhyiatul Fadilah5 (Chelonian Research Foundation, 2024)
Local wisdom is a valuable cultural heritage and needs to be preserved. One way to preserve it is to integrate it into learning. This research explores how the ethnoscience model can be applied in project-based learning to explore local wisdom. This research uses a qualitative approach. The data collection technique in this research is a literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation, and drawing conclusions. The research results show that the ethnoscience model is an effective tool for exploring local wisdom through project-based learning, which can be implemented by identifying local wisdom, organizing projects, combining knowledge, developing critical thinking skills, and implementing an ethnoscience approach. The ethnoscience approach can be carried out by reconstructing natural science in the customs and culture that exist in society to be developed into scientific science. Applying the ethnoscience model can help students understand scientific concepts, increase curiosity and interest in science, appreciate local wisdom, and develop 21st-century skills. Keywords: Local Wisdom, Project Based Learning, Ethnoscience Model